2017
DOI: 10.1186/s12937-017-0240-y
|View full text |Cite
|
Sign up to set email alerts
|

Diverse characteristics of the urinary excretion of amino acids in humans and the use of amino acid supplementation to reduce fatigue and sub-health in adults

Abstract: BackgroundThe excretion of amino acids in urine represents an important avenue for the loss of key nutrients. Some amino acids such as glycine and histidine are lost in higher abundance than others. These two amino acids perform important physiological functions and are required for the synthesis of key proteins such as haemoglobin and collagen.MethodsStage 1 of this study involved healthy subjects (n = 151) who provided first of the morning urine samples and completed symptom questionnaires. Urine was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
2
30
0
2
Order By: Relevance
“…The results for the amino acid concentrations in faux sweat from the current study (17 females, 30 males) and urine from an earlier study [52 females, average age ± SD of 35 ± 13.7; 99 males average age ± SD of 29.5 ± 11.8 (mean ± SD); Dunstan et al 2017] were used to model potential losses against the context of the reservoir of amino acids maintained in 3 L of circulating plasma calculated from data in Armstrong and Stave (1973). Rates of fluid loss via urination and faux sweat vary greatly between individuals but for modelling purposes a daily urinary volume of 1500 mL was used (Koushanpour and Kriz 1986) and two levels of faux sweat losses were calculated at rates less than the maximum sweating rates for humans at 1–2 L per hour during exercise (Torii 1995).…”
Section: Methodssupporting
confidence: 44%
See 4 more Smart Citations
“…The results for the amino acid concentrations in faux sweat from the current study (17 females, 30 males) and urine from an earlier study [52 females, average age ± SD of 35 ± 13.7; 99 males average age ± SD of 29.5 ± 11.8 (mean ± SD); Dunstan et al 2017] were used to model potential losses against the context of the reservoir of amino acids maintained in 3 L of circulating plasma calculated from data in Armstrong and Stave (1973). Rates of fluid loss via urination and faux sweat vary greatly between individuals but for modelling purposes a daily urinary volume of 1500 mL was used (Koushanpour and Kriz 1986) and two levels of faux sweat losses were calculated at rates less than the maximum sweating rates for humans at 1–2 L per hour during exercise (Torii 1995).…”
Section: Methodssupporting
confidence: 44%
“…Comparisons of the urine and sweat compositions from the two study groups revealed that histidine and glycine were the most highly abundant amino acids measured in both sweat and urine, where sweat also contained very high levels of serine in both males and females (Table 3). The total amino acid levels in urine did not vary significantly between males and females (Dunstan et al 2017) but the total level of amino acids in the faux sweat from females was significantly higher than that found in the males ( p  < 0.05). Under the scenario of a sedentary day with minimal exercise and no exposure to heat, the losses via faux sweat in males and females were lower than the estimated daily output from urine.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations